ChemInform Abstract: Rational Approaches, Design Strategies, Structure Activity Relationship and Mechanistic Insights for Anticancer Hybrids. Issue 23 (10th June 2014) - Nepali, Kunal; Sharma, Sahil; Sharma, Manmohan; Bedi, P. M. S.; Dhar, K. L.
Abstract Review: 534 refs.